OP0138 Novel Role of Mast Cells in the Regulation of Large Vessel Vasculitis. (10th June 2014) - Springer, J.; Raveendan, V.V.; Smith, D.; Maz, M.; Dileepan, K.
Abstract : Background: Our previous reports suggested that mast cell-mediated innate immune up-regulation plays a key role in vascular inflammation (1-2). The literature also document increased presence of mast cells in the temporal arteries of patients with giant cell arteritis, a type of large vessel vasculitis (LVV) (3). The activation of Toll-like receptor-4 (TLR4) has been implicated in the recruitment of dendritic cells and T-cells into the aortic wall in LVV. Endothelial cells, Th17 T-cells and macrophages produce interleukin 6 [IL-6] which is important in the pathogenesis of LVV. The mechanism by which mast cells modulate the pathogenesis of LVV is not known. Objectives: The objective of this study was to test the hypothesis that mast cell degranulation will regulate lipopolysaccharide (LPS, a TLR4 ligand)-induced systemic production of IL6. Methods: Two month old male C57BI6/J mice were randomized into 4 groups (N=4/group). They were injected intraperitoneally with saline (control), Compound 48/80 (mast cell degranulator, 1mg/kg), LPS (1mg/kg) or C48/80+LPS. Animals were sacrificed 24 h after injections, and serum IL-6 levels, aortic expressions of mRNAs encoding IL-6, TLR4 and suppressor of cytokine signaling-1 (Socs-1) were determined. Data were analyzed for statistical significance and p<0.05 was considered significant. Results: C48/80 injection did not increase serum levels of IL-6 or aortic expression of IL-6 mRNA compared to control. LPS injection significantly enhanced serum IL-6 (350±146 pg/ml vs 21.3±5.5 pg/ml) and aortic IL-6 gene expression (18.0±5.4 fold vs 1.03±0.025 fold). LPS-induced increase in serum IL-6 levels and IL-6 gene expression in the aorta were significantly reduced when mast cell degranulation was simultaneously induced by C48/80 (IL-6: 350±146 pg/ml vs 101±13 pg/ml; IL-6 mRNA: 18.0±5.4 vs 4.3±0.5 fold change). In comparison to controls, the aortic expression of Socs-1 mRNA was 2-fold and 3-fold higher in LPS-treated, and C48/80+LPS-treated mice, respectively. Aortic expression of TLR4 was not affected by any of the treatments. Conclusions: The results demonstrate that mast cell degranulation decreases aortic expression of IL-6 mRNA as well as systemic production of IL-6. The decreased expression of IL-6 was associated with increased expression of Socs-1 in aortic tissues. One mechanism by which mast cells regulate LPS-induced systemic production of IL-6 may be by inhibiting the expression of IL-6 mRNA in the vasculature through Socs-1 activation. Since mast cells release many immunomodulatory substances further studies are warranted to identify the regulatory factors. References: Talreja J, Kabir MH, Filla B, Stechschulte DJ, Dileepan KN. Histamine induces Toll-like receptor 2 and 4 expression in endothelial cells and enhances sensitivity to Gram-positive and Gram-negative bacterial cell wall components. Immunology. 113:224-33, 2004. Raveendran VV, Tan X, Sweeney ME, Levant B, Slusser J, Stechschulte DJ, Dileepan KN. Lipopolysaccharide induces H1 receptor expression and enhances histamine responsiveness in human coronary artery endothelial cells. Immunology. 132:578-88, 2011. Mayranpaa MI, Trosien JA, Nikkari ST, Kovanen PT. Mast cells associate with T-cells and neointimal microvessels in giant cell arteritis. Clin Exp Rheum. 26 (3 Suppl 49):S63-6, 2008. Acknowledgements: Supported by NIH grants R01-HL070101 & 3R01-HL070101-04S1, and Joseph & Elizabeth Carey Arthritis Fund and Audrey Smith Fund from KU Endowment Association. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2639